Urgensi Pengaturan Blokchain dalam Sistem Verifikasi E-Meterai pada Kontrak Digital di Indonesia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid adoption of digital contracts in Indonesia demands a reliable document authentication system, one of which is through electronic stamps (e-meterai). However, the current e-meterai verification system remains centralized and exclusively managed by Perum Peruri, making it vulnerable to single point of failure risks and data manipulation. Blokchain technology, with its characteristics of decentralization, transparency, and data immutability, offers a technical solution that could potentially strengthen the integrity of this verification system. This article aims to examine the legal position of blokchain technology within Indonesia's existing e-meterai regulatory framework and to analyze the urgency of establishing specific regulations governing its use. The research employs a normative juridical method through statutory and conceptual approaches. The findings reveal that blokchain currently occupies a legal grey area: technically compatible with the validity requirements of agreements under Article 1320 of the Civil Code and meeting the criteria for Electronic Information under Article 5 of the ITE Law, yet formally lacking explicit recognition due to its conflict with Perum Peruri's monopolistic authority established under Law Number 10 of 2020 on Stamp Duty. Four normative gaps are identified, encompassing the absence of evidentiary guarantees for blokchain-verified documents, the lack of mandatory standards for Electronic Certification Providers, the ambiguity in civil liability allocation for automated system failures, and the conflict between blokchain's immutability and the right to erasure under the Personal Data Protection Law. Comprehensive specific regulations constitute an urgent normative necessity to ensure legal certainty for Indonesia's digital contract ecosystem.